Pengaruh Instrumen Kebijakan Moneter terhadap Ketimpangan Pendapatan Nasional - Hastin Nurafni; Selfia Yuspita Sari; Risqianti Putri Pangestika; M. Yusuf Bahtiar (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the impact of monetary policy on income inequality in Indonesia over a certain period of time. Monetary policy implemented by Bank Indonesia plays an important role in maintaining macroeconomic stability through instruments such as interest rates, inflation, and the amount of money in circulation. However, the implementation of this policy also has an impact on the distribution of community income. This study uses a quantitative approach with secondary data in the form of time series analyzed using econometric regression methods to measure the effect of monetary policy variables on the income inequality index (Gini Ratio). The results of the study show that variables such as the benchmark interest rate and inflation have a significant relationship to income inequality. When inflation increases, the purchasing power of the lower middle class decreases more sharply than the upper class, thus widening the gap in inequality. Conversely, controlling inflation through appropriate interest rates can help reduce economic disparities. This study provides important meaning for policy makers to pay more attention to the distribution aspect in determining monetary policy so that economic growth can be more inclusive and equitable.